PERBANDINGAN METODE DOUBLE EXPONENTIAL SMOOTHING DAN TRIPLE EXPONENTIAL SMOOTHING PADA PERAMALAN NILAI EKSPOR DI INDONESIA - Puspita, Rindang Ndaru (Jambura Journal of Probability and Statistics, 2022)
Exports are a source of foreign exchange that can affect the level of the country's economy and become a benchmark in determining the quality of the country. The value of Indonesian exports expressed in US Dollars is a monthly fluctuating time series data. In an effort to control the value of Indonesia's exports, it is necessary to have the right strategy, one of strategies is forecasting the value of exports in the future. To determine an appropriate forecasting method, the MAPE results from the Double Exponential Smoothing and Triple Exponential Smoothing are compared. From the research, the results of the prediction of the value of Indonesia's exports for the next 7 periods, from June 2022 to December 2022, the most accurate after a comparison of the MAPE value is closest to zero, the result is Triple Exponential Smoothing method more accurate for forecasting the value of Indonesian exports, this is because historical data on the value of Indonesian exports shows a trend and seasonal pattern at the same time